State Supervision of Local Government Authorities - Jürgen Harbich (Central European Public Administration Review)
State supervision of local government authorities, a requirement of the rule of law, is discussed in relation to municipalities. State supervisory authorities are required to advise and support local government authorities. Supervision at various state levels takes place as legal supervision, which only includes the supervision of legality in matters of the municipality’s original competence, and as functional supervision that also supervises expediency in matters transferred by the state. The legality principle (intervention in all cases) is modified by the expediency principle (discretion). A number of remedies are available for implementing both legal and functional supervisory measures. Where municipalities consider that the supervisory measures, whether legal or functional, violate their rights of selfgovernment, they have recourse to the courts.